Study on thermal, water barrier and mechanical properties of polyurethane clay nanocomposite prepared by solution intercalation method - Norayuni, Azizi (2016)
In this thesis, a series of polyurethane (PU) nanocomposite was fabricated by using the solution intercalation polymerization by employing chloroform with the incorporation of nanoclay Cloisite B30. The interaction between the nanoclay Cloisite B30 and PU matrices is the major factor in determining the structure in the PU nanocomposite, which was aimed at achieving a good dispersion with slighter agglomerates. The thermal characterization was conducted through thermal conduction, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Thermal conductivity of the PU nanocomposite increased with increase in the nanoclay loading. The results show that there was significant effect of the nanoclay on lowering the melting temperature of the PU nanocomposite. Hence, the thermal degradation behaviour of PU increased by the incorporation of the nanoclay up to 16 oC for 96 % PU/4 % B30. The addition of the nanoclay results in the enhancement of the thermal stability. The morphology of PU nanocomposite was investigated using the field emission scanning emission microscopy (FESEM), scanning emission microscopy (SEM) and X-ray diffraction (XRD), while chemical structure analysis was analysed using Fourier transform infrared spectrometer (FTIR). FESEM micrographs demonstrated fewer agglomerates formed in the PU nanocomposite while an even distribution of nanoclay in SEM was obtained. The degree of crystallinity of PU nanocomposite was directly increased according to Cloisite B30 content, which shows that good intercalated structure has been attained. FTIR indicated that there was no chemical structure alteration in PU nanocomposite. The barrier properties of the PU nanocomposite films were studied through the water absorption and water permeability analysis. Water absorption analysis presented that the highest percentage of water absorption was in the 98% PU/2% B30 with 14.9 %. Meanwhile, the water permeability revealed an improvement through the increase in nanoclay loading due to the formation of the tortuosity of the transport path in the PU nanocomposite. The highest decrement in the water permeation rate amounting to 56 % for 3 bar and 68 % for 4 bars were obtained in 98% PU/2% B30 however for 2 bar, there was no volume of water penetrate through the sample. The tensile strength and elongation of the PU nanocomposite at break were improved by the incorporation of the nanoclay. The tensile stress for the pristine PU was valued at 0.40 MPa while the highest tensile stress at 0.93 MPa was observed for the sample with 96 % PU/4 % B30 film. Meanwhile, the percentage of the elongation at break of the sample is the maximum with 106 % for the sample with 96 % of PU/4 % of B30. The results exhibited that the tensile strength and elongation at break of the nanocomposites dramatically increased with the incorporation of the nanoclay. This improvement was dependent on the content of the nanoclay as well as the formation structure of the nanoclay in the PU matrices.